Penerapan Prinsip Akuntansi Syariah Dalam Transaksi Murabahah Pada Industri Perdagangan - Rusmini, Rusmini; Maulana, Ahnaf; Diantoro, Bagus Aldio (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2024)
Murabahah is a sale and purchase contract with a pre-agreed profit principle between the seller and the buyer. In a murabahah transaction, the seller and buyer must be clear and there is no element of fraud. Because the main principle of murabahah is transparency and fairness in transactions. The purpose of this paper is to determine and ensure that murabaha transactions are in accordance with sharia principles. This involves the avoidance of prohibited practices such as usury, gharar and maysir. The results of this study show the application of murabahah transactions using Islamic accounting principles. By applying Islamic accounting principles in murabahah transactions, it is expected that the trading industry can conduct business in a way that is in accordance with sharia principles, avoiding haraam practices, and providing accurate information and transparency to stakeholders